Shape matters: Ecomorphology Informs on Functional Traits and Diversity of Barents Sea Fish - Weber, Charlotte Teresa (Universitetet i Tromsø, 2014)
The Barents Sea (BS) is an arcto-boreal sea and one of the most productive areas adjacent to the Arctic, hosting many commercial fish stocks. As a result of climate change, temperature increases and a northward movement of several fish species in the BS have been reported, which will likely change community structures and ecosystem functioning. Hence, more information on ecosystem functioning need to be obtained to better understand the fish communities’ responses to stress. Ecomorphology relates shape directly to function. In this study, a landmark-based geomorphometric approach was chosen to assess the shape variation in the 72 most commonly observed fish species of the BS. The main shape differences were found in the location and the base-length of the anal and dorsal fins as well as in the overall body shape. Through differences in the location and the base length of the anal and dorsal fins, diet and habitat differences were identified as they are adaptations to environmental and ecological factors. Eel-like species as well as flatfish presenting long-based fins are usually associated with a benthic diet and demersal habitats. Small, streamlined fish with short-based anal and dorsal fins are more likely planktivores and pelagics. Biogeographic differences were found in the overall body shape, where eel-like, elongated fish are more often found in the arctic environment. But diet and habitat seemed to be the main drivers for shape variation whereas biogeography and temperature played a less important role. Functionally, large demersals and flatfish with long-based anal and dorsal fins distribute energy over large temporal and spatial scales and function as important links between lower and higher trophic levels. Eel-like fish with long-based anal and dorsal fins are very efficient in using locally abundant resources. Migratory species with streamlined bodies and short anal and dorsal fins, such as herring and capelin play an important role by transporting energy in the form of resources throughout the ...